The Impact of Risk Management on Project Success: A Field Study at Humanitarian Organizations in Yemen - Shujaa Aldeen, Mohammed Ahmed; Sarhan, Nashwan Abdulwahid (University of Science and Technology, Sana'a)
The study aimed to determine the impact of risk management (risk identification, risk analysis, risk response and risk monitoring and control) on project success (scope, schedule, cost and quality) at humanitarian organizations operating in Yemen (HOY). The study followed the analytical descriptive approach to meet its objectives. It utilized the simple random technique to select 15 organizations representing 127 HOY and the disproportional stratified random sampling technique to target the respondents. Data was collected through a printed questionnaire from 185 respondents who have roles in managing projects at the targeted organizations. The findings showed that risk management has a significant positive impact on project success. The findings also revealed that among 4 dimensions of risk management process, risk identification and risk monitoring and control were found as the most significant influencers that impact project success at HOY. The study recommends HOY to pay more attention to project risk management to attain higher project success level that ultimately contributes to the performance improvement and sustainability of their organizations. The study also recommends conducting more studies for further confirmations to the hypothesis of the study through testing the study’s variables at industries other than HOY such as banking industries and telecommunications companies.
Keywords: project success; risk management; humanitarian organizations